HEAVY METAL TOXICITY: LESSONS FROM A CASE OF SIMULTANEOUS OCCUPATIONAL EXPOSURE TO MANGANESE AND MERCURY. Issue 11 (9th October 2013) - Shribman, Sam; Davis, Angharad; Vella, Norbert; Giovannoni, Gavin
Abstract : Heavy metal toxicity represents a heterogenous group of rare diseases that are associated with a wide variety of neurological syndromes. Manganese and mercury are two heavy metals that are neurotoxic and have been associated with occupational exposures. Manganese toxicity is an established cause of Parkinsonism however the causal relationship with occupational exposures such as welding remains disputed. Chronic mercury toxicity is associated with the classic triad of tremor, gingivitis and erethism as well as visual, sensory and cerebellar disturbances. There are no well–defined therapeutic protocols for toxicity to mercury or many other heavy metals. We present a case of a 33 year–old male oil rig painter who regularly worked adjacent to active welding and did not take protective measures. His wife noticed that he was initially confused and then developed clumsiness, slurred speech, social withdrawal and hallucinations over the following year. On examination he had bilateral cerebellar signs, cognitive impairment and a chaotic intention tremor consistent with mercury toxicity. There were also symmetrical parkinsonian features including bradykinesia and rigidity in both upper and lower limbs with a cock–like walk typical of manganese toxicity. Blood mercury and manganese levels were both significantly raised. This case highlights the importance of considering a broad heavy metal screen in the context of neurological disease associated with industrial occupations. It also leads us to revisit the controversial association of welding and manganese exposure and then review sources of heavy metal exposures and the current recommendations for treatment.